2004
DOI: 10.1099/jmm.0.45661-0
|View full text |Cite
|
Sign up to set email alerts
|

Role of quorum sensing in the pathogenicity of Burkholderia pseudomallei

Abstract: Burkholderia pseudomallei is the causative agent of human and animal melioidosis. The role of quorum sensing (QS) in the in vivo pathogenicity of B. pseudomallei via inhalational exposure of BALB/c mice and intraperitoneal challenge of Syrian hamsters has not been reported. This investigation demonstrates that B. pseudomallei encodes a minimum of three luxI and five luxR homologues that are involved in animal pathogenicity. Mass spectrometry analysis of culture supernatants revealed that wild-type B. pseudomal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
102
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(105 citation statements)
references
References 46 publications
1
102
2
Order By: Relevance
“…In B. glumae, TofI-R regulates toxoflavin production, motility, protein secretion, and QsmR, an isocitrate lyase regulatortype transcriptional regulator (10)(11)(12). Less is known about gene control by C8-HSL in B. thailandensis via BtaI-R and B. pseudomallei via BpsI-R (13)(14)(15). In the present study, we found that QS induces cellular enzymes for production of oxalate (HOOC-COOH), which is excreted into the culture medium and likely shared by other members of the population, and as such is a public good.…”
mentioning
confidence: 99%
“…In B. glumae, TofI-R regulates toxoflavin production, motility, protein secretion, and QsmR, an isocitrate lyase regulatortype transcriptional regulator (10)(11)(12). Less is known about gene control by C8-HSL in B. thailandensis via BtaI-R and B. pseudomallei via BpsI-R (13)(14)(15). In the present study, we found that QS induces cellular enzymes for production of oxalate (HOOC-COOH), which is excreted into the culture medium and likely shared by other members of the population, and as such is a public good.…”
mentioning
confidence: 99%
“…1). Our genome analysis in silico indicated that the B. pseudomallei and B. mallei QS networks are genetically similar, and as with B. pseudomallei, B. mallei does not encode a putative LuxS system ( (34,35). It has been proposed that microbial species carrying multiple luxIR genes obtain these alleles through horizontal gene transfer (16).…”
Section: Discussionmentioning
confidence: 99%
“…For human and plant pathogens, AHL-based communication systems allow a microbial community to strategically induce or repress expression of genes, specifically alleles encoding putative virulence factors, in response to environmental stimuli. Several reports have identified functional QS systems in various Burkholderia species and have shown that these bacterial communication networks both positively and negatively regulate numerous extracellular virulence factors in addition to contributing to animal pathogenicity (B. cepacia) (1,3,20,21,31,34,36).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations